Factors associated with lack of prenatal care in a large municipality - Cristiane Quadrado da Rosa; Denise Silva da Silveira; Juvenal Soares Dias da Costa (Revista de Saúde Pública, 2014)
OBJECTIVE To analyze the factors associated with a lack of prenatal care in a large municipality in southern Brazil. METHODS In this case-control age-matched study, 716 women were evaluated; of these, 179 did not receive prenatal care and 537 received prenatal care (controls). These women were identified using the Sistema Nacional de Informação sobre Nascidos Vivos (Live Birth Information System) of Pelotas, RS, Southern Brazil, between 2009 and 2010. Multivariate analysis was performed using conditional logistic regression to estimate the odds ratios (OR). RESULTS In the final model, the variables associated with a lack of prenatal care were the level of education, particularly when it was lesser than four years [OR 4.46; 95% confidence interval (CI) 1.92;10.36], being single (OR 3.61; 95%CI 1.85;7.04), and multiparity (OR 2.89; 95%CI 1.72;4.85). The prevalence of a lack of prenatal care among administrative regions varied between 0.7% and 3.9%. CONCLUSIONS The risk factors identified must be considered when planning actions for the inclusion of women in prenatal care by both the central management and healthcare teams. These indicated the municipal areas with greater deficits in prenatal care. The reorganization of the actions to identify women with risk factors in the community can be considered to be a starting point of this process. In addition, the integration of the activities of local programs that target the mother and child is essential to constantly identify pregnant women without prenatal care.